Major determinants of cardiovascular disease risk among young adults - Nur Intan Hayati Husnul Khotimah; Sumbara Sumbara; Latifatul Khoirunnisa (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Cardiovascular disease (CVD) risk can be detected decades before onset, highlighting the importance of prevention beginning in young adulthood. Objective: This study aimed to identify the dominant factors associated with cardiovascular disease risk among young adults aged 19–40 years in Bandung City, Indonesia. Methods: This analytical cross-sectional study used primary data collected from 380 young adults aged 19–40 years residing in Bandung City, Indonesia, between July and September 2025. Participants were recruited using a snowball sampling technique. Data were collected using a modified version of the non-laboratory INTERHEART Risk Score (NL-IHRS). Results: Most participants had a moderate risk (56.1%). Significant associations were found between smoking, secondhand smoke exposure, BMI, and psychosocial problems (p = 0.000). Multivariate analysis identified secondhand smoke exposure as the strongest predictor (OR = 16.91; 95% CI: 8.13–44.90; p < 0.001), while low BMI and psychosocial support were protective. Conclusion: Secondhand smoke exposure was the dominant risk factor for cardiovascular disease among young adults, whereas healthy BMI and positive psychosocial support were protective factors. These findings provide evidence for strengthening early cardiovascular risk screening and targeted health promotion programs among young adults in Bandung City. Preventive interventions should prioritize reducing tobacco smoke exposure, promoting healthy body weight, encouraging regular physical activity, and enhancing psychosocial support through community-based and primary healthcare programs.